VIDEO CLIPS: A TOOL FOR ENHANCING STUDENTS’ LISTENING SKILLS - Sari, Farnia (Universitas Muhammadiyah Palembang, 2024)
The objective of this research was to investigate the impact of using video clip in the development of listening skills in an English as a Foreign Language (EFL) classroom. The study utilized an experimental research design with a quasi-experimental methodology. The participants of the study were the eleventh-grade students of SMA Ethika Palembang. Pretest and post-test data were collected from both the experimental group, which received video clips, and the control group, which received the lecturing method. Paired sample t-tests were used to analyze the pretest and posttest data, while independent sample t-tests were used to compare the post-test results between the two groups. The results of the paired sample t-test showed that both groups demonstrated improvement in their listening scores after the treatment. The analysis of the data revealed that there was a significant difference in the listening scores between the two groups.